Microstructure, Compressive Properties and Oxidation Behaviors of the Nb-Si-Ti-Cr-Al-Ta-Hf Alloy with Minor Holmium Addition - Qiaoli Wang; Yinan Xiao; Di Wu; Fang Yang; L.Y Sheng (Archives of Metallurgy and Materials)
In the present research, the Nb-Si-Ti-Cr-Al-Ta-Hf alloys with different Ho addition were prepared. Their microstructure, compressive properties and oxidation behaviors were investigated preliminarily. The results exhibit that the Nb-Si-Ti-Cr-Al-Ta-Hf alloy has coarse microstructure which is mainly composed of Nb solid solution, Nb5Si3 and Ti5Si3 phases. The minor Ho addition could refine the microstructure and suppress the precipitation of Ti5Si3 phase. Moreover, the Ho addition also leads to the formation of Ho2Hf2O7, which prefers to precipitate along the Nbss/Nb5Si3 phase interface. Compared with the Nb-Si-Ti-Cr-Al-Ta-Hf alloy, the minor Ho addition improves the room-temperature and high-temperature compressive properties of the alloy. Its room-temperature compressive strength and ductility obtain the maximum value of 1825 MPa and 16.5% when the Ho content is 0.1 at.%. Moreover, its best compressive strength at 873 K, 1273 K and 1473 K is 1495 MPa, 765 MPa and 380 MPa, respectively, when the Ho addition is 0.1 at.%. The oxidation behavior of the Nb-Si-Ti-Cr-Al-Ta-Hf alloy is diversified with the Ho addition. The oxidation rate of the alloy with 0.1 at.% Ho addition is the lowest while the alloy with 0.2 at.% Ho addition is the highest. Therefore, the 0.1 at.% Ho would be the appropriate content for the Nb-Si-Ti-Cr-Al-Ta-Hf alloy.